Implementing clinical ethics in German hospitals: content, didactics and evaluation of a nationwide postgraduate training programme. Issue 12 (26th November 2010) - Dörries, Andrea; Simon, Alfred; Neitzke, Gerald; Vollmann, Jochen
Abstract : The Hannover qualifying programme 'ethics consultation in hospitals', conducted by a four-institution cooperation partnership, is an interdisciplinary, scientifically based programme for healthcare professionals interested in ethics consultation services and is widely acknowledged by hospital managements and healthcare professionals. It is unique concerning its content, scope and teaching format. With its basic and advanced modules it has provided training and education for 367 healthcare professionals with 570 participations since 2003 (until February 2010). One characteristic feature is its attractiveness for health professionals from different backgrounds. Internationally, the Hannover programme is one of the few schedules with both academics and non-academics as target groups and a high participation rate of physicians. The concept of the Hannover programme is in great demand, and its schedule is continuously optimised through evaluation. The goals of enabling healthcare professionals from different professional backgrounds to define and reflect ethical problems, to facilitate and support the process of decision-making and to work out structures for their own institutions seem to have been achieved. However, in order to obtain effective and sustainable results, participation in the programme should be supplemented regularly by in-house training sessions or individual expert consultations. Future challenges include new thematic courses and providing a network for former participants, especially when they come from non-academic hospitals. The network is a reasonable platform to discuss participants' experiences, successes and pitfalls. A further task will be research on how the programme's concept can support the sustainability of ethics structures in the various institutions.